Density functional theory study on the properties of Cu-doped GaAs. (May 2020) - Ma, Deming; Cao, Yanyan; Zhang, Jinlong; Deng, Yufan; Wang, Wei; Li, Enling
Abstract: The electronic structure and optical properties of the sphalerite structured C u x G a 1 − x A s (x = 3.125%, 6.25% and 12.5%) were studied based on the first-principles method of density functional theory. The results show that the C u x G a 1 − x A s materials exhibit direct band-gaps, from valence band top to guide band low (solid blue line) i.e., 1.30 eV, 0.82 eV, 0.97 eV. It contains impurity levels in the middle, reaching the second transition. The calculated results also show that the energy required for electrons to jump from valence band to impurity levels, i.e., 0.42 eV, 0.36 eV, 0.31 eV. In addition, higher impurity levels resulted from copper doping reduces GaAs band-gaps in a great extent, which is beneficial to the transition and migration of electrons. At the same time, the static dielectric constant and refractive index of the doped system escalate with the increase of Cu doping ratio. Moreover, the absorption spectrum is red-shifted and the absorption of light is enhanced. In the system doped with 6.25% Cu, the electrons in Cu-3d orbital form a strong localization in the energy range of −3.9 eV ~ −1.8 eV. Indeed, the least influence on the complex dielectric function of the [010] is achieved when the ratio of doped Cu decreases to 3.125%, which makes the change of optical properties of the material in this crystal direction smaller than those in [100] and [001] orientations. The C u x G a 1 − x A s transition layer between GaAs devices and copper wires can substantially improve the electrode contact and subsequently the photoelectric characteristics of GaAs photoelectric devices. Graphical abstract: Image 1 Highlights: The results show that the band gap decreases after doping GaAs with Cu, which is beneficial to electron transition.. It is demonstrated that the static dielectric constant of the doping system escalate as the proportion of doped-Cu increases. The Cux Ga1-x As transition layer between GaAs devices and copper wires can substantially improve the electrode contact.